2016
DOI: 10.3390/nu8080449
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone, a Phytochemical of Subtropical Ginger, Protects against Hyperglycemia-Induced Retinal Damage in Experimental Diabetic Rats

Abstract: Diabetic retinopathy (DR), the most ordinary and specific microvascular complication of diabetes, is a disease of the retina. Zerumbone (ZER) is a monocyclic sesquiterpene compound, and based on reports, it is the predominant bioactive compound from the rhizomes of Zingiber zerumbet. The aim of the current study is to evaluate the protective effect of zerumbone against DR in streptozotocin (STZ)-induced diabetic rats. STZ-diabetic rats were treated with ZER (40 mg/kg) once a day orally for 8 weeks. ZER adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…Recent studies have shown that ZER can attenuate high‐fat diet‐induced hyperlipidemia and fatty liver through modulation of lipid metabolism (Tzeng, Liou, Chang, & Liu, ; Tzeng, Lu, Liou, Chang, & Liu, ). ZER also possesses protective effects on high glucose‐induced apoptosis in pancreatic β‐cells (Wang et al, ) and diabetes‐mediated retinal damage (Tzeng, Liou, Tzeng, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ZER can attenuate high‐fat diet‐induced hyperlipidemia and fatty liver through modulation of lipid metabolism (Tzeng, Liou, Chang, & Liu, ; Tzeng, Lu, Liou, Chang, & Liu, ). ZER also possesses protective effects on high glucose‐induced apoptosis in pancreatic β‐cells (Wang et al, ) and diabetes‐mediated retinal damage (Tzeng, Liou, Tzeng, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…], [7] and the contribution of the transannularly conjugated dipolar formula 3 to its structure and chemistry, [8] made us wonder whether the presence of the carbonyl group could provide an electronic finesse and/or the necessary preorganization of the cycloundecatriene system to trigger aconcerted transannular cyclization and breach the Eolefin barrier. [9] Since 2 shows potent activity in animal models of human chronic degenerative diseases like cancer, [10] diabetes, [11] and arthritis, [12] and is also of relevance for perfumery, [13] the structural context for probing this concept was not only mechanistically appealing,but also relevant for medicinal and lifestyle related applications. [9] Since 2 shows potent activity in animal models of human chronic degenerative diseases like cancer, [10] diabetes, [11] and arthritis, [12] and is also of relevance for perfumery, [13] the structural context for probing this concept was not only mechanistically appealing,but also relevant for medicinal and lifestyle related applications.…”
Section: In Memory Of Giovanni (Jacques) Casiraghimentioning
confidence: 99%
“…[4] To avoid the formation of endocyclic E-configured double bonds in unsaturated rings smaller than cyclooctene,asituation topologically impossible, [5] the cyclization of 1,a na ll-E-configured cyclo-undecatriene,m ust follow ap athway that involves all three double bonds in ac oncerted fashion. [9] Since 2 shows potent activity in animal models of human chronic degenerative diseases like cancer, [10] diabetes, [11] and arthritis, [12] and is also of relevance for perfumery, [13] the structural context for probing this concept was not only Figure 1. [4] Ther eady availability of the 8-oxo derivative of ahumulene (zerumbone; 2)f rom at ropical ginger [Zingiber zerumbet (L.) Roscoe ex Sm.…”
mentioning
confidence: 99%
“…We envisioned that, after carbonyl activation with an electrophilic reagent ( A , Figure ), the crossed dienone system could undergo electrocyclization in a Nazarov fashion to an allyl cation ( B ), thus in effect removing the E ‐olefin barrier to intramolecular cyclization and paving the way to an interrupted Nazarov reaction course (Figure ) . Since 2 shows potent activity in animal models of human chronic degenerative diseases like cancer, diabetes, and arthritis, and is also of relevance for perfumery, the structural context for probing this concept was not only mechanistically appealing, but also relevant for medicinal and lifestyle related applications.…”
Section: Figurementioning
confidence: 99%